Distribution of NADPH-diaphorase and expression of nNOS, N-methyl-D-aspartate receptor (NMDAR1) and non-NMDA glutamate receptor (GlutR2) genes in the neurons of the hippocampus after domoic acid-induced lesions in adult rats - Ananth, C (WILEY-LISS, 2020)
HIPPOCAMPUS